Rrp6: Integrated roles in nuclear RNA metabolism and transcription termination. (26th November 2015) - Fox, Melanie J.; Mosley, Amber L.
Abstract : The yeast RNA exosome is a eukaryotic ribonuclease complex essential for RNA processing, surveillance, and turnover. It is comprised of a barrel‐shaped core and cap as well as a 3′–5′ ribonuclease known as Dis3 that contains both endo‐ and exonuclease domains. A second exonuclease, Rrp6, is added in the nucleus. Dis3 and Rrp6 have both shared and distinct roles in RNA metabolism, and this review will focus primarily on Rrp6 and the roles of the RNA exosome in the nucleus. The functions of the nuclear exosome are modulated by cofactors and interacting partners specific to each type of substrate. Generally, the cofactor TRAMP (Trf4/5–Air2/1–Mtr4 polyadenylation) complex helps unwind unstable RNAs, RNAs requiring processing such as rRNAs, tRNAs, or snRNAs or improperly processed RNAs and direct it toward the exosome. In yeast, Rrp6 interacts with Nrd1, the cap‐binding complex, and RNA polymerase II to aid in nascent RNA processing, termination, and polyA tail length regulation. Recent studies have shown that proper termination and processing of short, noncoding RNAs by Rrp6 is particularly important for transcription regulation across the genome and has important implications for regulation of diverse processes at the cellular level. Loss of proper Rrp6 and exosome activity may contribute to various pathologies such as autoimmune disease, neurological disorders, and cancer. WIREs RNA 2016, 7:91–104. doi: 10.1002/wrna.1317 This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein–RNA Interactions: Functional Implications RNA Processing > 3' End Processing RNA Turnover and Surveillance > Turnover/Surveillance Mechanisms